2012
DOI: 10.1186/1532-429x-14-57
|View full text |Cite
|
Sign up to set email alerts
|

A non-invasive clinical application of wave intensity analysis based on ultrahigh temporal resolution phase-contrast cardiovascular magnetic resonance

Abstract: BackgroundWave intensity analysis, traditionally derived from pressure and velocity data, can be formulated using velocity and area. Flow-velocity and area can both be derived from high-resolution phase-contrast cardiovascular magnetic resonance (PC-CMR). In this study, very high temporal resolution PC-CMR data is processed using an integrated and semi-automatic technique to derive wave intensity.MethodsWave intensity was derived in terms of area and velocity changes. These data were directly derived from PC-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
57
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 22 publications
0
57
0
Order By: Relevance
“…Biglino et al performed wave intensity analysis using CMR in the ascending and descending aorta in healthy controls, patients with coronary heart disease [9] and congenital heart disease [28]. They demonstrated that wave intensity in the aorta was feasible using phase contrast CMR, with temporal wave intensity profiles that were in keeping with previously demonstrated invasive profiles, however they did not compare the technique with invasive data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biglino et al performed wave intensity analysis using CMR in the ascending and descending aorta in healthy controls, patients with coronary heart disease [9] and congenital heart disease [28]. They demonstrated that wave intensity in the aorta was feasible using phase contrast CMR, with temporal wave intensity profiles that were in keeping with previously demonstrated invasive profiles, however they did not compare the technique with invasive data.…”
Section: Discussionmentioning
confidence: 99%
“…WIA has recently been successfully performed using CMR in the ascending and descending aorta [9], however it has never been attempted in the highly-mobile, small-caliber, tortuous coronary arteries, nor has it been directly compared to invasively acquired data. Accordingly, we assessed the feasibility of coronary WIA using CMR and compared to invasive measures in the same patients.…”
Section: Introductionmentioning
confidence: 99%
“…used tool for analyzing hemodynamics in the time domain (2,6,12,13,15,22,34,39,43,47). More recently, three alternative definitions of wave intensity have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, three alternative definitions of wave intensity have been proposed. For settings where noninvasive measurements of blood velocity and vessel diameter (D) or vessel area (A) are available (e.g., echocardiography and phase contrast MRI), Feng and Khir (9) proposed the use of dDdU, Tanaka et al (42) advocated d[lnD]dU, while Biglino et al (2) used d[lnA]dU. Although similar to wave intensity, these quantities have units of m 2 /s, m/s, and m/s, respectively, whose physical meaning is unclear in this context (the term "wave intensity" was retained, even though the units were no longer those of intensity).…”
Section: Discussionmentioning
confidence: 99%
“…This has been done because no major viscous effects were expected in the current setting and because the study was focusing on the feasibility of the setup and pulmonary measurements. A commonly used blood analogue is a solution of water and glycerine with a volume percentage of 33.5% glycerine [2,5,29], which could be easily employed in this setting.The RPA-LPA flow distribution, governed by the downstream resistances, was similar to the normal in vivo flow distribution of 55-45% [30] and the RPA/LPA ratio of 1.18 corresponds to a ratio of 1.1 ± 0.2 for the adult human pulmonary circulation at rest [31]. The pressure for the IPVR scenario (33.8 ± 0.2 mm Hg) was within the range of PAH and was significantly higher than the pressure for the healthy scenario.…”
mentioning
confidence: 99%